Analysis of Community Willingness to Pay in Waste Management - Putra Budi Ansori (Asean International Journal of Business, 2023)
This article examines the public's willingness to pay, considering that the local revenue data from the waste levy has not reached the 2022 target, while population growth, economic growth and changes in consumption patterns have experienced changes that affect the amount of waste generation in the city of Pekanbaru.The purpose of this study is to analyze the effect of education, income and work community on willingness to pay in waste management. The sample is 100 heads of families. The sampling technique is done by purposive sampling. The results of the hypothesis test show that the education variable and the job variable do not significantly influence expenses. While income is proven to have a significant effect on paying expenses. It was also found that simultaneously the variables of education, income and work influence the awareness of paying. Furthermore, it is obtained that payment receipts are influenced by changes in the values of education, income, and employment variables of 31.9% while 68.1% are determined by other variables that are not in this research model.